Numerical comparison of several a posteriori error estimators for 2D stress analysis - Beckers, Pierre; Zhong, Hai-Guang; Maunder, Edward (European Journal of Computational Mechanics, 1993)
The reliabilities of several a posteriori error estimaJors, including those of Gaga, Zienkiewicz-Zhu, and more recently those proposed by Beckers and Zhong are compared through a set of examples in plane elasticity. The examples range from those having analytic solutions to those having progressively stronger singularities. The examples generally use either 4 (or 8) node quadrilaterals for initial comparisons. The results of these examples indicaJe that, in certain cases, some of the error estimators are unreliable and do not appear to be asymptotically exact. Further studies are suggested to investigate the general validity of the initial conclusions.